KAJIAN AWAL MEKANISME REAKSI ELEKTROLISIS NaCl MENJADI NaClO4 UNTUK MENENTUKAN TAHAPAN REAKSI YANG EFEKTIF DARI PROSES ELEKTROLISIS NaCl - Prianto, Bayu (Indonesian Journal of Aerospace, 2007)
Ammonium Perchlorate is the oxidizer commonly used in propellant. Ammonium Perchlorate compose from ammonium cation (NH4) and perchlorate anion (ClO4). Perchlorate anion can be synthesized from chloride anion (from NaCl solution) by using electrochemical method. Studying of electrochemical mechanism reaction of perchlorate is very important, because ammonium perchlorate is strategic material. With the knowledge of electrochemical mechanism of perchlorate, we will get information of electrochemical reaction process condition, than can be used to do chemical synthesis in the laboratory. Pre-study the mechanism reactions have done by studying of several reaction models. All model reaction is tested by chemical computation method to find effective and eficient reaction model (represented by reaction energy value) From three tested models, we obtained the 3rd model was the effective and eficient reactions to produce perchlorate. The value of Gibbs free energy reaction for hyphochlorite, 240.190 kcal per mol, and 263.974 kcal per mol respectively. Keywords: Elektrolysis, Ammonium Perchlorate, Gibbs reaction.